Analisis Penilaian Komponen Bangunan Gedung terhadap Pemeliharaan Ruang Kelas SMK Negeri 3 Balikpapan - Sari, Oryza Lhara; Rifai, Danisa Amalia (Universitas Ibn Khaldun, 2023)
SMK Negeri 3 Balikpapan is a SMA/SMK equivalent level school that has the most classroom facilities in the entire City of Balikpapan. However, there was some damage to the classrooms caused by several factors such as the age of the building, natural factors, planning factors and others. So that the quality of the building will certainly affect the condition of the classroom and the comfort of the classroom users. Based on these problems, the solution that can be done is to carry out maintenance of the classroom building in order to maintain the function of the classroom and the condition of the classroom building remains functional and provide a sense of security and comfort for classroom users. This study aims to determine the building components that need to be reviewed for maintenance of the classrooms of SMK Negeri 3 Balikpapan, especially those that affect the condition of the classrooms and the comfort of classroom users, namely for students and teachers of SMK Negeri 3 Balikpapan. The method used in this research is to conduct a literature study, a preliminary survey by conducting observations and interviews with experts in the field of building construction and analysis using the calculation of item scores on the cut-off value of the building maintenance variable indicators. The results of the analysis show that the cut-off value obtained is 3.30 points with 14 relevant maintenance variables and indicators affecting classroom conditions and classroom user comfort, including architectural components (X1) with 6 indicators, structural components ( X2) with 2 indicators, mechanical components (X3) with 2 indicators, electrical components (X4) with 3 indicators and outdoor building components (X5) with 1 indicator. Then there is the variable indicator of classroom maintenance which has a level of relevance with the highest score obtained on the indicators of ceiling maintenance (X11), door and window maintenance (X12) and wall maintenance (X22), with a score of 4.4 pointsKey words: Building Maintenance, Classrooms, Classroom Users